Legal Principles of Taxation in Russia: Essential Reflection in Legislation - S. D. Kazachenkov (Финансы: теория и практика, 2020)
The present paper aims to study the nature of taxation principles in Russia and analyze how they are structured and outlined in the legislation. The research is based on general scientific research methods, such as the comparative method and the method of system analysis. The study provides a comparative analysis of the views of Russian and foreign scientists regarding the system of taxation principles and the provisions of the current legislation in the field of taxes. The results of the paper offer that a significant amount of research has been devoted to the problem of the essential reflection of taxation principles but it has not been sufficiently developed and updated. The author argues the need to consolidate the principles of taxation in the current legislation by introducing a special chapter in the Tax Code of the Russian Federation, justifies the need for a fair formation of a system of taxation principles in theoretical and practical aspects. The types and structure of taxation principles in the modern world are proposed. A special chapter has been developed, which the author suggests introducing into the Tax Code of the Russian Federation. The author concluded that in order to reflect the basic principles of taxation in the current tax legislation, it is necessary to introduce the proposed changes.